A STUDY ON CUSTOMER SATISFACTION ON SELECTED MOBILE NETWORKS IN CUDDALORE - KANAGARAJU, Dr.P.; KARTHIKEYAN, R. (The journal of contemporary issues in business and government, 2021)
Mobile service is one of the largest industries in the world. In this market, competition is on the rise through economic opening. The region's use of mobile telephones was promoted by private companies. It's the consumer demand today for telecom networks. Mobile providers must take note of customer opinions and deals on the market. Mobile providers must identify customers ' desires and influence the factors before developing any service or deal. In this context, the research document focuses on the factors which are most relevant to customers when using mobile service providers. Telecom is one of the main infrastructure markets of our country, the government of India said. The study was done in a well-structured schedule. The public telecommunications sector was able to achieve universal service to all the villages protected by global class standards under economic liberalization, privatization and competition politics in India and make the broadcasting of telecommunications open. The purpose of this paper is to analyze the customer satisfaction on different types of mobile service providers and widely used mobile network in cuddalore.